Efficient authentication scheme for cross-trust domain of IoV based on double-layer shard blockchain - Xuejiao LIU; Qiang ZHONG; Yingjie XIA (Tongxin xuebao)
To solve the problems of poor scalability, slow synchronization of authentication information, and high authentication overhead in cross-trust domain message authentication in the Internet of vehicles (IoV), an efficient authentication scheme for cross-trust domain of IoV based on a double-layer shard blockchain was proposed.A double-layer shard blockchain architecture was designed for lots of cross-trust domain message authentication by constructing blockchains on different entity levels in all domains to improve the scalability of the system and ensure secure and efficient sharing of cross-domain information.A blockchain sharding method based on the Metis graph partitioning algorithm for IoV was proposed to balance loads of each shard and adapt to the uneven distribution of authentication information on different road segments in IoV, thereby improving the efficiency of synchronizing a large number of authentication information on the chain.A batch authentication scheme based on certificateless public-key cryptography (CL-PKC) was proposed, which reduced the authentication overhead of cross-domain messages by enabling batch authentication of messages from different trust domains.Experimental results show that the proposed scheme effectively improves the authentication efficiency of cross-trust domain messages.Compared with other schemes, the proposed scheme reduces the computational overhead of a large number of cross-domain message authentication by more than 26.4%.